Fibromyalgia, Depression, and Autoimmune Disorders: An Interconnected Web of Inflammation - Stefania Sedda; Maria Piera L. Cadoni; Serenella Medici; Elena Aiello; Gian Luca Erre; Alessandra Matilde Nivoli; Ciriaco Carru; Donatella Coradduzza (Biomedicines, 2025)
Background: Fibromyalgia, depression, and autoimmune diseases represent a triad of interconnected conditions characterized by overlapping biological pathways, including chronic inflammation, immune dysregulation, and neurochemical imbalances. Understanding their shared mechanisms offers opportunities for innovative therapeutic approaches. Objective: This systematic review explores the common inflammatory- and immune-related pathways among these conditions, emphasizing their implications for biomarker development and novel therapeutic strategies. Methods: Following PRISMA guidelines, a comprehensive literature search was conducted in databases including PubMed, Scopus, Web of Science, and the Cochrane Library. Studies examining the relationship between fibromyalgia, depression, and autoimmune diseases with a focus on immune responses, inflammatory biomarkers, and therapeutic interventions were included. The quality of the selected studies was assessed using the Cochrane Risk of Bias tool. Results: From the 255 identified studies, 12 met the inclusion criteria. Evidence supports the role of pro-inflammatory cytokines (e.g., IL-6, TNF-α) and neurochemical dysregulation (e.g., serotonin, dopamine) as key factors in the pathophysiology of these conditions. Pilot studies highlight the potential of immune-modulating therapies, including low-dose IL-2 and anti-inflammatory agents such as N-acetylcysteine and minocycline, in alleviating both physical and psychological symptoms. Emerging biomarkers, including cytokine profiles and platelet serotonin activity, show promise for personalized treatment approaches. Conclusions: The shared inflammatory pathways linking fibromyalgia, depression, and autoimmune diseases underscore the need for integrated therapeutic strategies. Although pilot studies provide preliminary insights, validation through large-scale, multicenter trials is essential. Future research should focus on standardizing methodologies and leveraging biomarker-driven precision medicine to improve outcomes for patients with these complex, multifactorial conditions.